Migration and Influencing Factors of Auto Rice Mill Workers' Intentions to Stay in Villages: An Empirical Study in Selected Areas of Dinajpur District (Journal of the Bangladesh Agricultural University, 2025)
The study aims to explore the impact of urban-rural migration on the socio-demographic, economic, and occupational dynamics influencing the lives of workers in rural communities, particularly those employed in auto rice mills in the Dinajpur district of the Rangpur division, Bangladesh. It investigates the socio-economic challenges faced by auto rice mill workers in rural Bangladesh, with a specific focus on their migration patterns and the factors that influence their decision to stay in rural areas. This study utilized a structured questionnaire to gather data from 245 workers, Q-methodology to explore subjective perspectives to identify key influencing factors, and correlation analysis to examine the relationships between socio-demographic factors and workers' intentions to stay in villages. The analysis reveals a predominantly male-headed, middle-aged workforce, with significant educational disparities and a strong reliance on full-time industrial employment. Migration emerged as a key factor, with nearly 69% of workers relocating to access better job opportunities. Despite economic benefits, extended working hours and inadequate amenities highlight the precarious nature of their livelihoods. Key challenges identified include insufficient support from government and non-government organizations, limited access to credit, and a lack of essential resources such as food and clothing. Correlation analysis underscores the impact of various factors on workers' intentions to remain in villages. Physical factors, including housing and infrastructure, and welfare factors, such as access to utilities and healthcare, play a pivotal role in improving retention. Social, educational, and occupational factors also exhibit significant influence, with better conditions leading to greater satisfaction and prolonged stays in rural areas. The findings have important policy implications. Aligning with the Sustainable Development Goals (SDGs), interventions should focus on improving educational opportunities (SDG 4), promoting gender equity (SDG 5), ensuring decent work conditions (SDG 8), and enhancing rural infrastructure (SDG 9). Addressing food security (SDG 2), access to clean water and energy (SDGs 6 and 7), and reducing inequalities (SDG 10) are also critical. By fostering partnerships and leveraging multi-sectoral approaches (SDG 17), these measures can drive inclusive development, improve workers' quality of life, and ensure sustainable progress in rural communities. The study underscores the need for comprehensive strategies that address both immediate challenges and long-term socio-economic goals.J Bangladesh Agril Univ 23(1): 71–84, 2025